Oxytocin normalizes altered circuit connectivity for social rescue of the Cntnap2 knockout mouse - Choe, Katrina Y.; Bethlehem, Richard A. I.; Safrin, Martin; Dong, Hongmei; Salman, Elena; Li, Ying; Grinevich, Valéry; Golshani, Peyman; DeNardo, Laura A.; Peñagarikano, Olga; Harris, Neil G.; Geschwind, Daniel H. (Neuron, 2022)
The neural basis of abnormal social behavior in autism spectrum disorders (ASDs) remains incompletely understood. Here we used two complementary but independent brain-wide mapping approaches, mouse resting-state fMRI and c-Fos-iDISCO+ imaging, to construct brain-wide activity and connectivity maps of the Cntnap2 knockout (KO) mouse model of ASD. At the macroscale level, we detected reduced functional coupling across social brain regions despite general patterns of hyperconnectivity across major brain structures. Oxytocin administration, which rescues social deficits in KO mice, strongly stimulated many brain areas and normalized connectivity patterns. Notably, chemogenetically triggered release of endogenous oxytocin strongly stimulated the nucleus accumbens (NAc), a forebrain nucleus implicated in social reward. Furthermore, NAc-targeted approaches to activate local oxytocin receptors sufficiently rescued their social deficits. Our findings establish circuit- and systems-level mechanisms of social deficits in Cntnap2 KO mice and reveal the NAc as a region that can be modulated by oxytocin to promote social interactions.
Available online 20 December 2021
Gesehen am 17.05.2022